2D Materials: Layer Dependence and Light Tuning Surface Potential of 2D MoS2 on Various Substrates (Small 14/2017). Issue 14 (April 2017) - Li, Feng; Qi, Junjie; Xu, Minxuan; Xiao, Jiankun; Xu, Yuliang; Zhang, Xiankun; Liu, Shuo; Zhang, Yue
Abstract : In article number 1603103, Yue Zhang and co‐workers demonstrate light tuning of the surface potential of two dimensional MoS2 which is attributed to the photovoltaic effect, the produced numbers of photogenerated electrons by incident light will transfer between the metal substrate and MoS2, then form the local electric field at the interface. The local electric field can change the numbers of trapped charges on the surface of MoS2 .